Interleukin-33 (IL-33): A critical review of its biology and the mechanisms involved in its release as a potent extracellular cytokine. (August 2022) - Cayrol, Corinne; Girard, Jean-Philippe
Highlights: Discussion of the biology of the alarmin cytokine IL-33, a member of the IL-1 family with critical roles in type 2 and type 1 immunity and regulatory responses, and allergic and non-allergic inflammation. Review of the expression of IL-33 in tissue-derived cells (endothelial cells, epithelial cells and stromal cells), its rapid release upon tissue injury or cellular damage, and its processing into highly active forms by inflammatory and allergen proteases. Discussion of the problems of specificity of IL-33 reagents, critical review of the recent literature and highlights of results validated using IL-33-deficient cells as controls. Recommendations for generating reliable results by including appropriate specificity controls early in a project in each experimental system and model analyzed. Review of the genetic and environmental regulation of IL-33 in asthma, and results of clinical trials with anti-IL-33 antibodies for therapy of asthma and COPD. Abstract: Interleukin-33 (IL-33), a member of the IL-1 family, is an alarmin cytokine with crucial roles in tissue homeostasis and repair, type 2 immunity, allergic and non-allergic inflammation, viral infection, and cancer. IL-33 is abundant in the nuclei of tissue-derived cells, including endothelial cells from blood vessels, epithelial cells from barrier tissues, and fibroblastic stromal cells from various tissues. IL-33 is released upon cell damage or tissue injury and activates Myd88-dependent signaling pathways in cells expressing the ST2 (IL-1RL1) receptor. Analysis of patient samples and studies in murine models support an important role of IL-33/ST2 signaling in allergic inflammation in different tissues (lung, nasopharynx, skin) and diseases (asthma, chronic rhinosinusitis, allergic rhinitis, atopic dermatitis). IL33 and IL1RL1/ST2 are among the most highly replicated susceptibility loci for asthma. However, the IL-33/ST2 pathway is also important in non-allergic inflammation. Indeed, targets of IL-33 include immune cells involved in both type 2 and type 1 immunity and regulatory responses, such as group 2 innate lymphoid cells (ILC2s), mast cells, regulatory T cells (Tregs), Th2 cells, basophils, eosinophils, macrophages, dendritic cells (DCs), neutrophils, Th1 cells, CD8 T cells, NK and iNKT cells. In the main part of this review, we discuss the basic biology of the IL-33 protein (molecular characteristics, nuclear localization, cellular sources in vivo ), and its mechanisms of release, and bioactive forms in various contexts. Importantly, we alert the scientific community to the problems of specificity of IL-33 reagents, we explain why studies without specificity controls with IL-33-deficient cells are misleading to the field and lead to unnecessary controversy, and we make recommendations to generate reliable results. In the final part, we review the genetic and environmental regulation of IL-33 in allergic airway inflammation and asthma, and we highlight recent studies showing clinical efficacy of anti-IL-33 antibodies in asthma and chronic obstructive pulmonary disease (COPD).